The causes and evolutionary consequences of mixed singing in two hybridizing songbird species (Luscinia spp.) - Vokurková, Jana; Petrusková, Tereza; Reifová, Radka; Kozman, Alexandra; Mořkovský, Libor; Kipper, Silke; Weiss, Michael; Reif, Jiří; Dolata, Paweł T; Petrusek, Adam (PloS one, 2013)
Bird song plays an important role in the establishment and maintenance of prezygotic reproductive barriers. When two closely related species come into secondary contact, song convergence caused by acquisition of heterospecific songs into the birds' repertoires is often observed. The proximate mechanisms responsible for such mixed singing, and its effect on the speciation process, are poorly understood. We used a combination of genetic and bioacoustic analyses to test whether mixed singing observed in the secondary contact zone of two passerine birds, the Thrush Nightingale (Luscinia luscinia) and the Common Nightingale (L. megarhynchos), is caused by introgressive hybridization. We analysed song recordings of both species from allopatric and sympatric populations together with genotype data from one mitochondrial and seven nuclear loci. Semi-automated comparisons of our recordings with an extensive catalogue of Common Nightingale song types confirmed that most of the analysed sympatric Thrush Nightingale males were 'mixed singers' that use heterospecific song types in their repertoires. None of these 'mixed singers' possessed any alleles introgressed from the Common Nightingale, suggesting that they were not backcross hybrids. We also analysed songs of five individuals with intermediate phenotype, which were identified as F1 hybrids between the Thrush Nightingale female and the Common Nightingale male by genetic analysis. Songs of three of these hybrids corresponded to the paternal species (Common Nightingale) but the remaining two sung a mixed song. Our results suggest that although hybridization might increase the tendency for learning songs from both parental species, interspecific cultural transmission is the major proximate mechanism explaining the occurrence of mixed singers among the sympatric Thrush Nightingales. We also provide evidence that mixed singing does not substantially increase the rate of interspecific hybridization and discuss the possible adaptive value of this phenomenon in nightingales.
Keywords: molekulární evoluce; genetické lokusy; zpívání; Sympatry; mužské pohlaví; fenotyp; Phenotype; Singing; Animals; ženské pohlaví; zvířata; Hybridization, Genetic; sympatrie; Passeriformes; hybridizace genetická; Genetic Loci; Female; Male; Evolution, Molecular